The emergency medical services network’s response to the COVID-19 pandemic in Albania - Persiani, Niccolò; Giusti, Martina; Taiti, Francesco; Biancalani, Andrea; De Luca, Michele; Caldés Pinilla, Maria José (Frontiers in Public Health, 2025)
BackgroundDuring the COVID-19 pandemic, healthcare systems worldwide have implemented many health emergency plans to address the crisis. Following initial predominantly hospital-centred approaches, community-based healthcare assistance emerged as a more effective response to the emerging population needs. In low-middle-income countries, and particular in the so-called transition countries, the adaption the complexities of integrating pre-hospital and in-hospital Emergency Medical Services (EMSs) have been particularly challenging due to the absence of a consolidated network among these services. This research aimed to evaluate the emergency healthcare services response to covid-19 pandemic in Albania, as significant transition country.MethodThe country case study methodology was deemed the most fitting approach for this research. Albania was selected as a notable case study due to its continuous endeavours towards achieving national welfare aligned with European standards, especially in the healthcare sector, as it has been moving towards pre-adhesion to the European Union.ResultsAlbanian EMSs network demonstrated its capability to update over time the national strategical plan against COVID-19 pandemic according to emerging evidence and the related organizational issues to effectively satisfy population health needs. This adaptability became feasible with the introduction of a modern EMSs system, comprising both pre-hospital and in-hospital dimensions. These two components collaborated and are still collaborating to implement integrated healthcare pathways, each with distinct responsibilities, resources, and protocols.ConclusionThe development, consolidation, and collaboration between pre-hospital and in-hospital EMSs implemented in Albania have played a crucial role in preventing the collapse of the healthcare system in the face of the COVID-19 pandemic. Albanian experience provides valuable insights for the reform or to build up EMSs network and healthcare systems in transition countries, drawing upon the lessons learned from the challenges posed by the COVID-19 pandemic.